A pharmacist-managed virtual consult service for patients with rheumatologic conditions requiring specialty or infused medications. (25th June 2021) - Sasnovskaya, Veranika; Kumor, Lisa M; Stubbings, JoAnn; Chevalier, Aimee
Abstract: Purpose: To describe a pharmacist-managed virtual consult service practice model for rheumatology patients and evaluate its initial impact on compliance with institutional critical care guidelines for biologic response modifiers (BRMs). Summary: Pharmacologic care of patients with rheumatologic conditions often revolves around the use of BRMs. While these drugs are generally well tolerated, nearly all of them carry risks for serious adverse events. The severity of these possible problems necessitates a thorough initial and ongoing clinical workup. Based on results of a needs assessment, a virtual consult service was introduced at the University of Illinois Hospital and Health Sciences System (UI Health) in August 2018 to integrate clinical, specialty pharmacy, and therapeutic infusion services for proactive medication and safety management of patients with rheumatologic conditions requiring treatment with BRMs. The consult service was managed by an embedded clinical pharmacist and a postgraduate year 1 specialty pharmacy resident, who evaluated each request for therapy appropriateness prior to submission for insurance approval. Conclusion: Forty-one percent of the pharmacy benefit consult orders required a pharmacist intervention prior to referral to the specialty pharmacy. All consults (100%) adhered to the safety management guidelines for BRMs after review by the pharmacist. The pharmacist-managed virtual consult service is a novel practice model in specialty pharmacy that permits pharmacists to manage multiple patients simultaneously, virtually, and with optimal impact on medication selection and management at or before the point of prescribing.